Job satisfaction and job commitment among secondary school teachers in Osun state, Nigeria (2016)
The paper investigated the correlation between variables of job satisfaction and the three types of job commitment among secondary school teachers. An ex post facto survey research design was adopted. A multi-stage sampling technique was used to select 540 secondary school teachers from the three political senatorial districts of Osun State. Job Descriptive Index Scale (r=.82) and Organizational Commitment Scale(r=.79) were used to collect responses from teachers. The data collected were analysed using Pearson's correlation coefficient and multiple regression analysis. Findings showed that job satisfaction correlated positively with affective, continuance and normative commitments. Pay, work itself, supervision and co-workers have significant positive relationships with job commitment while promotion has negative relationship with job commitment. It was recommended that supervisors in the teaching profession should pay attention to person-job material needs and aspiration of teachers to sustain their commitment. Government should provide beautiful architectural work environment to facilitate commitment.